Optimizing Cropping Pattern And Water Productivity: The Case Of Upper Awash Agro Industry Enterprise Irrigation Scheme - Dinsefa, Shafi (ASTU, 2019)
Scarcity of water during critical irrigation period has intensified at Upper Awash Agro Industry Enterprise irrigation scheme. In addition, adoption of poor irrigation water management and fixed cropping pattern make the scheme low productive in terms of yield, profit and water. The aim of this study was to maximize the net profit of scheme due efficient utilization of the scarce resource among the competing crops through optimizing cropping pattern and water productivity. Irrigation water demand and water productivity in terms of total (effective rainfall plus irrigation), irrigation and crop evapotranspirated water for current cropping pattern of annual crop were assessed. The considered annual crops were tomato, maize, dry beans and cotton. Their irrigation water demand was determined using CROPWAT8.0 model and compare with supplied water; finally nonlinear programming model (NLP) using crop water production function were developed to determine the optimal cropping pattern that gives maximum profit at different crop water allocation scenario. The models applied under full and five different levels of deficit crop water requirement scenario (10%, 20%, 30%, 40% and 50%). Profit maximization being the objective function of the NLP models, monthly and annual irrigation water availability, total land availability, the maximum possible area for tomato due to processing factory capacity and production costs are constraints; area allocation and irrigation water demand of each crop are decision variables. The program solved by Lingo17.o optimization software. The result shows that from the month of July to September, the supply meets the irrigation demand but from month of October to March and end of April to June, supply cannot meet the demand. Water productivity (WP) is expressed in physical and economic term. Physical and economic productivity of tomato, maize, dry bean and cotton in terms of crop evapotranspirated water were 7.57, 0.77, 0.25, 0.35 kg/m3 and 29.66, 0.90, 0.0 and 2.80 ETB/m3 respectively. These crop evaptranspirated water productivity values of all crops were higher than total and irrigated water productivity except cotton. For most of crops, the physical productivity in terms of total, irrigation and crop water were below the world average value. The optimal cropping pattern developed under full , 10, 20, 30, 40 and 50% CWR deficit scenario were reduced their total optimal cropping pattern by 48.4, 51, 45.6, 37.3, 54 and 44.4% compared to the existing cropping pattern. However, their net profit and average water productivity increased by 50.80, 33.66, 16.18, 0.33, -13.61 and -22.37% and 80.1, 70.3, 70.1, 51.8, 166.8 and 151.4% respectively compared to existing pattern. Water productivity level of 40 and 50% CWR deficit scenario was very high but with regard to net profit, they were far from the optimal. The optimal cropping pattern developed under full CWR scenario gave the maximum total profit as well as optimum WP compared to existing and all other scenarios. In conclusion, Total optimal cropping pattern in each scenario uses less than 60 % of current irrigation land due to water constraints. However, to irrigate all the existing irrigation land by scientific irrigation strategy, extra water sources are will be needed.
Keywords: optimization, cropping pattern, water productivity, net profit, non linear programming